2016
DOI: 10.1080/13880209.2016.1257031
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided fractionation and identification of α-amylase inhibitors from Syzygium cumini leaves

Abstract: Context: Pancreatic α-amylase and α-glucosidase inhibitors serve as important strategies in the management of blood glucose. Even though Syzygium cumini (L.) Skeels (Myrtaceae) (SC) is used extensively to treat diabetes; scientific evidence on antidiabetic effects of SC leaves is scarce. Objective: SC leaf extract was investigated for α-amylase inhibitory effect and continued with isolation and identification of α-amylase inhibitors. Materials and methods: Bioassay-guided fractionation was conducted using in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
(35 reference statements)
3
22
0
1
Order By: Relevance
“…Hence the respective inhibitors may have the ability to retard the catalysis by binding to the free enzyme as well as to the enzymesubstrate complex. In agreement with the previous findings of Poongunran et al (2016), higher inhibitory effects were observed with methanol and water extracts as the V max values obtained were lower and the K m values were higher when compared with those of ethyl acetate extracts.…”
Section: Kinetics Of α-Amylase Inhibitionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence the respective inhibitors may have the ability to retard the catalysis by binding to the free enzyme as well as to the enzymesubstrate complex. In agreement with the previous findings of Poongunran et al (2016), higher inhibitory effects were observed with methanol and water extracts as the V max values obtained were lower and the K m values were higher when compared with those of ethyl acetate extracts.…”
Section: Kinetics Of α-Amylase Inhibitionsupporting
confidence: 92%
“…However, kinetics of these inhibitory effects were not studied previously. Results on amylase inhibitory effects of the present study were in agreement with the results of Poongunran et al (2016). Lineweaver-Burk plots were produced with the data obtained in the presence of ethyl acetate ( Figure 6A), methanol ( Figure 6B) and water ( Figure 6C) mixed type inhibitory effects on α-amylase by the three extracts as K m and V max differed from those of the control sample [in the absence of inhibitory effects (0)].…”
Section: Kinetics Of α-Amylase Inhibitionsupporting
confidence: 88%
“…C) in UA‐administered flies compared to controls, improving the energy resources and hence the climbing ability of aged male w 1118 flies. Although UA exhibits inhibitory effects on porcine α‐amylase and yeast α‐glucosidase activity in vitro glucose levels were not lowered but enhanced by UA intake in male fruit flies, indicating srl ‐mediated glucose upregulation by UA.…”
Section: Discussionmentioning
confidence: 89%
“…e authors suggested a possible relationship between amylase inhibition and the presence of phenolic compounds. Poongunran et al [28], working with dried leaves of Syzygium cumini, found that extracts of methanol and water had high α-amylase inhibitory activity (98.3 ± 2.3 and 98.6 ± 1.6, respectively). e authors reported that the strong inhibition of the enzyme is due to the presence of oleanolic acid and ursolic acid, isolated from the leaves of Syzygium.…”
Section: Inhibition Of α-Amylasementioning
confidence: 99%
“…In addition to luteolin, Karthic et al [39] and Poongunran et al [28] describe in their studies the presence of other α-amylase and α-glycosidase inhibitors in seeds and leaves of Syzygium cumini, respectively. ey are betulinic acid, ursolic acid, and oleanolic acid, all with molecular weight of 456.7 g/mol.…”
Section: Maldi-tof Spectroscopy Analyses Were Performed Inmentioning
confidence: 99%